THE PYROPHANITE-ECANDREWSITE SOLID-SOLUTION: CRYSTAL STRUCTURES OF THE MN1-XZNXTIO3 SERIES (0.1 ≤ X ≤ 0.8) - Mitchell R.H.; Liferovich R.P. (My University, 2004)
The crystal structure of members of the pyrophanite-ecandrewsite solid-solution series, Mn1-xZnxTiO3 (0.1 less than or equal to x less than or equal to 0.8 apfu). synthesized by ceramic methods in air at ambient pressure, has been characterized by Rietveld analysis of powder X-ray-diffraction patterns. All of these compounds crystallize with the ilmenite structure and adopt space group R (3) over bar. The maximum solubility of Zn in MnTiO3 is considered to be similar to0.8 apfu Zn, as compounds with greater Zn content do not form. Data are given for cell dimensions and atom coordinates, together with bond lengths, Volumes and distortion indices for all coordination polyhedra. Within the solid-solution series, unit-cell parameters and volumes decrease linearly from those of MnTiO3 with increasing ZnTiO3 content. All compounds consist of distorted AO(6) and TiO6 polyhedra, and, in common with pyrophanite and ilmenite, the former are the more distorted. Displacement of (Mn,Zn) and Ti from the centers of their coordination polyhedra increases with increasing Zn content. The interlayer distance across the vacant octahedral site in the TiO6 layer decreases with entry of the smaller Zn cation into the AO(6) octahedra. The synthetic titanates are analogues of iron-free manganoan ecandrewsite and zincian pyrophanite occurring in peralkaline syenites at Pilansberg, in South Africa, and Pocos de Caldas, in Brazil.
Keywords: ecandrewsite; pyrophanite; titanate; order; ilmenite group; distorted octahedra; crystal structure; Rietveld refinement